The Impact of Interactive Learning Media on Students’ Learning Interest - Reni Pista Saragih; Mendarissan Aritonang; Alfonsus Situmorang (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study discusses the effect of interactive learning media on eighth-grade students at SMP GKPI Padang Bulan. The research method applied was a quasi-experimental design. Based on the results of the study, the average score of the final learning interest questionnaire in the experimental class was 86.26, while the control class obtained an average score of 62.90. It was found that the Asymp. Sig. (2-tailed) value was < 0.001. Since the significance value was smaller than 0.05, it can be concluded that Ha was accepted and H0 was rejected. Therefore, the study indicates that the use of interactive learning media in science subjects, particularly on the topic of the solar system, significantly influences the learning interest of eighth-grade students at SMP GKPI Padang Bulan.